2015
DOI: 10.1007/s00418-015-1376-5
|View full text |Cite
|
Sign up to set email alerts
|

Galanin regulates blood glucose level in the zebrafish: a morphological and functional study

Abstract: The present study has demonstrated the galaninergic innervation of the endocrine pancreas including sources of the galaninergic nerve fibers, and the influence of galanin receptor agonists on blood glucose level in the zebrafish. For the first time, a very abundant galaninergic innervation of the endocrine pancreas during development is shown, from the second day post-fertilization to adulthood. The fibers originated from ganglia consisting of galanin-IR, non-adrenergic (non-sensory) neurons located rostrally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 80 publications
(106 reference statements)
1
11
0
Order By: Relevance
“…Both juvenile (25 days post fertilization; dpf) and adult (1 year old) zebrafish display dense innervation networks within the endocrine pancreas ( Figure 1E–F ). By 25 dpf, the celiac ganglion provides sympathetic innervation ( Figure 1E ), as previously described ( Podlasz et al, 2016 ), and at this stage intra-pancreatic innervation between the primary and secondary islets is also present ( Figure 1E ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Both juvenile (25 days post fertilization; dpf) and adult (1 year old) zebrafish display dense innervation networks within the endocrine pancreas ( Figure 1E–F ). By 25 dpf, the celiac ganglion provides sympathetic innervation ( Figure 1E ), as previously described ( Podlasz et al, 2016 ), and at this stage intra-pancreatic innervation between the primary and secondary islets is also present ( Figure 1E ).…”
Section: Resultssupporting
confidence: 80%
“…Parasympathetic innervation predominates prior to 5 dpf, but by 25 dpf, sympathetic innervation extending from the celiac ganglia was also detected. Galaninergic nerves have been previously identified in the zebrafish pancreas ( Podlasz et al, 2016 ), and as in non-human primates these nerves are parasympathetic ( Verchere et al, 1996 ). The neurons present on the periphery of the islet as revealed in our studies could give rise to the peri-endocrine nerve plexus which has been observed in rodents ( Tang et al, 2014 ; Ushiki and Watanabe, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this possibility, it was recently shown that the embryonic zebrafish islet is innervated at the relevant time points, and that a neurotransmitter, namely galanin expressed in these neurons, is involved in blood glucose regulation. 59,60 Notably, the delayed glucose response in the isolated zebrafish islets is similar to that seen in mammalian islets. While this delay is attributed to the time taken for glucose diffusion and metabolism, 61,62 it might be further affected by the cleavage of neural connection during the islet isolation procedure.…”
Section: Discussionmentioning
confidence: 66%
“…Hence, our results imply that NAX‐5055 mediates its anticonvulsant effect without changing cerebral glucose metabolism that may ultimately lead to unwanted side effects. Notably, using NAX‐5055 as a pharmacological tool, GalR1 activation was shown to increase systemic blood glucose levels in mice and zebra fish (Flynn and White, ; Podlasz et al, ). The peripheral hyperglycaemia induced by NAX‐5055 might influence cerebral glucose metabolism in vivo as it has been demonstrated that glucose transporters and particularly GLUT‐1 in the blood‐brain barrier are regulated by ambient glucose concentrations (Vannucci et al, ).…”
Section: Discussionmentioning
confidence: 99%